Transformasi Plasmid GFP (Green Fluorescent Protein) ke Bakteri Endofit Potensial K2 dan K8 dari Pisang Klutuk (Musa accuminata colla) - Vika Manda Putri; Yasir Sidiq; Triastuti Rahayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the results of GFP (Green Fluorescent Protein) transformation into potential endophytic bacterial isolates K2 and K8 from Klutuk banana (Musa accuminata colla). The method used is exploratory with data analysis conducted qualitatively and descriptively through literature review. The results showed that GFP transformation into potential endophytic bacterial isolates K2 and K8 from Klutuk banana was successful, evidenced by the presence of green fluorescent signals under UV light. This transformation is also beneficial for tracking the colonization of endophytic bacteria within plant tissues. The GFP plasmid pYL101C-sfGFP used has a total size of 6682 bp and contains a gene resistant to Gentamicin (GMC). In conclusion, GFP transformation on potential endophytic bacterial isolates K2 and K8 was successfully carried out and provides significant benefits in tracking endophytic bacterial colonization. Keywords: Endophytic Bacteria, Gentamicin, GFP, Klutuk Banana, GFP Plasmid Transformation